Separation of powers and antitrust - Martenet, Vincent (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2024)
Separation of powers and antitrust deal with power and occupy centre stage in our challenging, digital times, but their interactions have not yet been analysed. This timely and ground-breaking book provides an innovative cross-disciplinary analysis of the potential convergence of these two fields. Notably, Vincent Martenet examines the concentration of politico-economic power in the hands of a few digital firms which have adopted private regulation, impacting an entire industry and society at large. He combines doctrinal method with historical developments, case studies, assessment of legislative proposals, and observations on the functioning of digital markets and democracy in the digital era. The book sketches important new axes of the separation of powers and suggests that antitrust may contribute, albeit in a limited way, to greater trust in both society and democracy: 'antitrust for trust', the ultimate apparent antitrust paradox.
Power -- Economic content of the separation of powers theories? -- Political content of antitrust from a historical perspective -- Political content of antitrust in the digital era -- Separation of powers in antitrust -- Antitrust in separation of powers -- general issues -- Promises and shortcomings of recent or proposed legislation -- New politico-economic axes of the separation of powers -- New institutional and individual axes of the separation of powers.
Title from publisher's bibliographic system (viewed on 29 Sep 2023).
Keywords: Antitrust law -- Political aspects